Emerging role of interaction between m6A and main ncRNAs in gastrointestinal (GI) cancers - Xu, Yating; Yu, Xiao; Guo, Wenzhi; He, Yuting (Frontiers in Immunology, 2023)
As a prevalent epigenetic modification, the role of m6A has been increasingly highlighted in the alteration of numerous RNAs implicated with multiple biological processes, such as formation, export, translation, and degradation. With the advancement of transcriptome sequencing technologies, it was found that most genes are unable to translate to protein and only a minority belong to coding genes. Accumulating evidence shows that these non-coding genes play pivotal roles in regulating physiological function and pathological mechanisms of disease. The mutual association and interplay of m6A and ncRNAs also deserve further discussion. Thus, we analyzed and summarized how ncRNAs affect the regulators of m6A and by what means the expression of ncRNAs is altered via m6A in gastrointestinal cancers. We focused on the effect of the interaction of m6A and ncRNAs on the molecular mechanisms of malignant behavior in gastrointestinal cancers, specifically concluding potential targets for early diagnosis, exact prognosis and effective treatment.